Anteroventral third ventricle lesions impair cardiovascular responses to intravenous hypertonic saline infusion - Pedrino, G. R.; Sera, CTN; Cravo, S. L.; Colombari, DSD (Elsevier B.V., 2005)
The anteroventral third ventricle (AV3V) region is a critical area of the forebrain, acting on fluid and electrolyte balance and maintaining cardiovascular homeostasis. The purpose of this study was to determine the effects of lesions to the anteroventral third ventricle region on cardiovascular responses to intravenous hypertonic saline (HS) infusion, Male Wistar rats were anesthetized with urethane. The femoral artery and jugular vein were cannulated to record mean arterial pressure (MAP) and infuse hypertonic saline (3M NaCl, 0.18 mL/100 g bw, over 1 min), respectively. Renal blood flow (RBF) was recorded by ultrasonic transit-time flow probes. Renal vascular conductance (RVC) was calculated as renal blood flow to mean arterial pressure ratio and expressed as percentage of baseline. After hypertonic saline infusion in sham animals, renal blood flow and renal vascular conductance increased to 137+10% and 125+7% (10 min), and 141 +/- 10% and 133 +/- 10% (60 min), respectively. Increases in mean arterial pressure (20-min peak: 12 +/- 3 mm Hg) were also observed. An acute lesion in the AV3V region (DC, 2 mA 25s) 30 min before infusion abrogated the effects of hypertonic saline. Mean arterial pressure was unchanged and renal blood flow and renal vascular conductance were 107 +/- 7% and 103 +/- 6% (10 min), and 107 +/- 4 and 106 +/- 4% (60 min), respectively. Marked tachycardia was observed immediately after lesion. Responses of chronic sham or lesioned rats were similar to those of acute animals. However, in chronic lesioned rats, hypertonic saline induced sustained hypertension. These results demonstrate that integrity of the AV3V region is essential for the renal vasodilation that follows acute changes in extracellular fluid compartment composition. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: renal blood flow; rats; AV3V region; hypertonic saline; blood pressure